FIRST RECORD OF THE RED SWAMP CRAYFISH PROCAMBARUS CLARKII (GIRARD, 1852) (CRUSTACEA, DECAPODA, CAMBARIDAE) IN PERU: ITS OCCURRENCE IN THE PANTANOS DE VILLA, LIMA, PERU - Mogollón, Valentín (2021)
The presence of the red swamp crayfish, Procambarus clarkii (Girard, 1852), a species native to the central and southern United States of America and northeastern Mexico, is reported in the Los Pantanos de Villa wetland, representing its first record in the continental waters of Peru. This species has a marked ecological plasticity, which gives it a strong invasive character that has made it one of the most widely distributed freshwater crabs in the world. It is omnivorous and opportunistic, being able to change its diet according to the body of water where it is established, which together with a short life cycle and great facility to increase its population, represents a potential threat to native species and natural ecosystems. Fish and birds are its main predators. In Los Pantanos de Villa it has been found in the Vista Alegre, Ganaderos and Huaylas channels, between September 22, 2019 and May 1, 2021.